Gdy pisarz staje się dziennikarzem. Kilka uwag o „Gazecie Pisarzy” - Ślawska, Magdalena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2018)
The article stems from a media linguistic perspective and serves as a case study for comparing the roles of a journalist and a writer. The author chose a textual experiment for that purpose, namely the 23-24 April 2016 edition of Gazeta Wyborcza, a Polish daily. On that day the paper turned into Writers’ Newspaper and was prepared in full by several dozen writers from Poland and abroad. The project’s aim was to promote reading the press and literature. The author analysed metatextual and paratextual elements along with self-commentaries regarding the project. The results show the experiment indicated the communicative specificity of the journalistic profession: the particularities of the editorial office, the importance of the topic, of character limits and fact-checking. As a communication experiment, the newspaper underlined the interactive nature of the modern-day press and its openness to the reader.